PENGARUH LINGKUNGAN KERJA TERHADAP PRESTASI KERJA PEGAWAI PADA KANTOR KESYAHBANDARAN DAN OTORITAS PELABUHAN KELAS IV BIMA - Muh Badar; Firmansyah Kusumayadi; Yohanes Durman (Jurnal Nusa Manajemen, 2024)
This study aims to determine the Influence of the Work Environment on Employee Work Performance at the Port Master's Office and Class IV Bima Port Authority. The approach used in the study is an associative approach. The population in the study amounted to 40 people with a sample of 30 people. The data collection techniques used were observation, questionnaires, and literature studies. The data analysis technique used was simple linear regression analysis, processed using the Statistical Product and Service Solution (SPSS) version 20 program. The results of the study showed that the Work Environment had a significant effect on Employee Work Performance at the Port Master's Office and Class IV Bima Port Authority.